The Writing Program Administrator as Interstitial Radical - Farmer, Frank (Radical Teacher, 2018)
Drawing upon personal experience as a writing program administrator at a research university, and marshaling a body of critical scholarship that examines how neoliberal ideology in the academy might be opposed, the author discusses interstitial resistance in the form of a curricular alternative--namely, the outsider genre of zines. Because zines typically embody a "worldview dramatically at odds with the [one] cultivated and reinforced by institutions of higher education," zines offer students an alternative point of view not usually found in standard writing curricula. While the author uses zines as a central illustration, the purpose here is to encourage readers to find the "cracks and fissures" in their own institutions so that the insinuations of neoliberal policies might be resisted through teaching and administrative initiatives.